Doxycycline reduces osteopenia in female rats - Figueiredo, Fellipe A. T. de; Shimano, Roberta C.; Ervolino, Edilson [UNESP]; Pitol, Dimitrius L.; Gerlach, Raquel F.; Issa, Joao Paulo M. (Nature Publishing Group, 2019)
Doxycycline, a member of the tetracycline family, is a drug used as an antibiotic (dosage of 100 mg/day) and as an anti-inflammatory drug on the dosage of 20 mg twice a day, this use has Matrix Metalloproteinases (MMP) inhibitor action. Doxycycline is a calcium chelator and therefore interferes in bone remodeling. The main objective of this study was to evaluate the action of the drug doxycycline in the control of osteopenia. Sixty three Wistars rats were divided into 9 groups with n=7 each, as follow: the control group with doxycycline 10 mg/kg/day (C10), control with doxycycline 30 mg/kg/day (C30) and control (C), ovariectomized group with doxycycline 10 mg/kg/day (OVX10), ovariectomized with doxycycline 30 mg/kg/day (OVX30), and ovariectomized with water (OVX), sedentary group with 10 mg/kg/day (Se10), sedentary with doxycycline 30 mg/kg/day (Se30), and sedentary group with water (Se). Left femoral bone was used for bone densitometry, right femoral bone for histological analysis. The right tibia was intended for chemical quantifications, the total serum was used for cholesterol and calcium quantification. The length of the left femoral bone was measured after the densitometry analysis. Statistical analysis was performed using multivariate general linear model (ANOVA two factors with Bonferroni adjustment) and the TRAP analysis was subjected to normality test and then were subjected to nonparametric test, both with p < 0.05 significance. Statistically significant differences were found, with better results for the groups exposed to the medication (10 and 30 mg/kg/day): Se vs. Se10 and Se vs. Se30 for BMC, quantification of magnesium, amount of cancellous bone in the distal portion; OVX vs. OVX10 for BMC, BMD and calcium in serum; OVX vs. OVX10 and OVX30 for quantification in proximal and distal portion of cancellous bone; Se vs. Se30 and OVX vs. OVX30 for immunostaining for TRAP, all results with minimum of p <= 0.05. Doxycycline had a deleterious effect on control groups and positive action for bone organization on female rats affected by bilateral ovariectomy-induced osteopenia and sedentary lifestyle.